UPAYA PENINGKATAN HASIL BELAJAR SISWA DALAM MATA PELAJARAN KEWARGANEGARAAN MELALUI METODE PEMBELAJARAN ROLE PLAYING (BERMAIN PERAN) PADA SISWA KELAS XII IPA.4 SMAN 1 KINALI - Uhkfi Hendri (JURNAL MANAJEMEN PENDIDIKAN, 2018)
Abstract Based on the learning outcomes of students of Class XII IPA.4 SMAN 1 Kinali in the subjects of Citizenship found that student learning outcomes in the subjects of Citizenship is still very low. The average student learning outcomes are still under the KKM. The purpose of this study is to describe and obtain information about efforts Improving student learning outcomes in subjects Sub-nationality Displays a positive attitude towards Pancasila as an open ideology through Role Playing Learning Methods (Role Playing) in Class XII IPA.4 SMAN 1 Kinali West Pasaman District. This research is a classroom action research. The research procedures in this research include planning, action, observation and reflection. This study consists of two cycles with four meetings. The subjects consisted of 35 students of Class XII IPA.4 SMAN 1 Kinali. The data were collected using observation sheet and daily test. Data were analyzed using percentages. Based on the results of research and discussion that have been put forward, it can be concluded that Role Playing Learning Method (Role Playing) can improve student learning outcomes in subjects Sub-nationality Displays a positive attitude towards Pancasila as an open ideology SMAN 1 Kinali. Student learning outcomes from cycle I to cycle II. Student learning outcomes in cycle I was 60.43 (Enough) increased to 85.46 (Good) with an increase of 25.04%. Keywords: Learning Outcomes, Citizenship, Learning Methods Role Playing (Role Playing)